3-Hydroxy-3-m-Sulphonato (Sodium Salt) Phenyl-1-o-Nitrophenyltriazene: An Indicator for the simultaneous Complexometric Determination of Cr(III) with Fe(III), Cu(II) and Ni(II) - Ressalan, S.; Chauhan, R.S.; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2012)
3-Hydroxy-3-m-sulphonato(sodium salt) phenyl-1-o-nitrophenyltriazene as an indicator for the simultaneous complexometric determination of Cr(III), Fe(II) and Ni(II) in binary and ternary metal ion mixtures has been studied. The presence of 20-fold excess of eleven diverse cations and anions did not interfere with the determination of 5.2 mg of Cr(III), The amount of metal ions found was in good agreement with the amount of metal ions actually present; so the determinations are quite accurate. This established hydroxytriazene as a metallochromic indicator for the complexometric determination of Cr(III).